Environmental Enrichment During Adolescence Acts as a Protective and Therapeutic Tool for Ethanol Binge-Drinking, Anxiety-Like, Novelty Seeking and Compulsive-Like Behaviors in C57BL/6J Mice During Adulthood - Rodríguez-Ortega, Elisa; de la Fuente, Leticia; de Amo, Enedina; Cubero, Inmaculada (Frontiers in Behavioral Neuroscience, 2018)
Repetitive drug/ethanol (EtOH) binge-like consumption during pre-addictive stages favors a transition to addiction in vulnerable organisms. Experimental evidence points to the therapeutic and preventive effects of environmental enrichment (EE) on drug and EtOH addiction; however, little is known regarding EE modulation of binge-like consumption in non-dependent organisms. Here, we explore the impact of early EE on binge-like EtOH consumption: (1) we test whether early EE exposure prevents binge-like EtOH intake (20% v/v) in adult mice under an intermittent drinking in the dark (iDID) schedule; (2) we evaluate the therapeutic effects of EE housing conditions on binge-like EtOH consumption in adult animals; and (3) we compare novelty-seeking and compulsive-like behaviors, and anxiety-like behavior, as measured by the Hole Board (HB) and Elevated Plus Maze (EPM) tests, respectively, in adult EE/standard environment (SE) animals. Adolescent (postnatal day 28; PND28) mice were randomly allocated to two housing conditions (4 animals/cage): EE or SE. At PND67 all the animals were exposed to a schedule of EtOH binge-like iDID. On PND92 half of the animals in each environmental condition (EE and SE) were randomly allocated to two subgroups in a crossover design, where environmental conditions were kept similar to those previously experienced or switched, finally leading to four experimental conditions: EE-EE, EE-SE, SE-SE, and SE-EE. EtOH binge-like consumption continued until PND140, when EPM and HB tests were finally conducted. The main observations were: (1) EE-reared mice showed lower EtOH binge-like intake than SE-reared mice during adulthood, which supports a protective role for EE. (2) when adult EtOH drinking SE-reared mice were switched to EE conditions, a reduction in EtOH binge-like consumption was observed, suggesting a therapeutic role for EE; however, losing EE during adulthood triggered a progressive increase in EtOH binge-like intake. Moreover, (3) EE-housed adult animals with long-term exposure to EtOH binge-drinking showed lower anxiety-like, compulsive-like, and novelty-seeking behaviors than SE-housed mice, irrespective of the specific housing conditions during adolescence. We discuss the primary impact of EE on anxiety-like neurobehavioral brain systems through which it secondarily modulates EtOH binge-like drinking.